(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Currently, the prevalence of allergic diseases in different countries is steadily increasing. The study of the mechanisms of the immunomodulatory action of dental materials is a very relevant new scientific direction of modern materials science. This article presents literature data describing the pathogenetic features of the effect of synthetic dental materials used in the manufacture of dental prosthetic structures on the oral mucosa in patients with allergic intolerance.